2009
DOI: 10.1590/s0102-695x2009000200012
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of Herissantia crispa (L.) Brizicky

Abstract: RESUMO: "Atividade biológica da Herissantia crispa (L.) Brizicky". O extrato metanólico bruto (EMeOH) das partes aéreas da Herissantia crispa (L.) Brizicky, planta rica em flavonóides e que não possui estudos farmacológicos, foi testada para avaliar sua atividade sob os parâmetros comportamentais e determinar a dose letal 50 (DL 50 ) em camundongos; atividade antimicrobiana e antiulcerogênica. O EMeOH (5000 mg/kg, v.o. ou 2000 mg/kg i.p.) não alterou os parâmetros comportamentais e não causou mortes nos animai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
(30 reference statements)
0
3
0
1
Order By: Relevance
“…HCl caused severe damage to the gastric mucosa, while ethanol produces lesions necrosis with action necrosis directly reducing factors such defensive secretion of bicarbonate and mucus production (Alrashdi, et al, 2012), and increased acid secretion (Lima, et al, 2009). Ranitidine is an H2 receptor antagonist role in reducing gastric acid secretion by inhibiting the binding of histamine H2 receptor selectively (Aziz, 2002).…”
Section: Gastro Protector Activitymentioning
confidence: 99%
“…HCl caused severe damage to the gastric mucosa, while ethanol produces lesions necrosis with action necrosis directly reducing factors such defensive secretion of bicarbonate and mucus production (Alrashdi, et al, 2012), and increased acid secretion (Lima, et al, 2009). Ranitidine is an H2 receptor antagonist role in reducing gastric acid secretion by inhibiting the binding of histamine H2 receptor selectively (Aziz, 2002).…”
Section: Gastro Protector Activitymentioning
confidence: 99%
“…Traditionally, it is used in India for treatment of asthma, cough, diabetes, ulcers, and jaundice [8]. This plant is rich in flavonoids but has not been well studied with regard to pharmacology [9]. One of the studies found that Abutilon crispum L. Medik can be used as an anti-inflammatory agent through in vivo experiments, but the exact mechanism remains unknown [10].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, this study aims to contribute to the inception of a therapeutic option, particularly from natural sources, which can be effective in removing the main signs and symptoms of inflammation and pain, diminishing the problems related to drug resistance and the various toxic and side effects caused by drugs currently available. Herissantia crispa, known as malvaísco, belongs to the Malvaceae family [1] and various effects are related to this plant: antiulcer [2], antimicrobial [2] and antinociceptive [3]. The aim of this study was to evaluate the anti-inflammatory activity and participation of the glutamatergic system in the antinociceptive effect of the ethyl acetate phase of Herissantia crispa (FAEHc).…”
Section: Introductionmentioning
confidence: 99%